The λ pattern on time-RR interval scatter plot of neonatal ambulatory ECG: a marker of transient bradycardia - Li, Hualian; Wei, Xin; Zhu, Fengna; Zheng, Fei; Yu, Tingting (Frontiers in Cardiovascular Medicine, 2025)
BackgroundNeonatal bradycardia often triggers transient escape rhythms that challenge clinical diagnosis, with current methods lacking dynamic biomarkers for risk stratification.ObjectiveTo validate the λ pattern, a heart rate dynamic signature on time-RR interval scatter plot, for distinguishing escape rhythms from transient sinus bradycardia and predicting recovery timelines in neonates.MethodsRetrospective analysis of 36 neonates (≤28 days) with 24 h electrocardiogram (ECG) monitoring. Holter data identified λ patterns (abrupt ≥20% RR prolongation and >3 s gradual recovery). Reverse-engineering ECG validated rhythm origins. Survival models assessed λ burden-prognosis correlations.Results487 λ patterns (15.5 ± 3.2/neonate) were detected: 80.3% escape rhythms, 19.7% sinus bradycardia. High λ burden (≥21/24 h) predicted delayed recovery vs. low burden (≤10/24 h) [HR = 4.22 (95% CI: 1.98–9.01), p < 0.0001]. All cases resolved spontaneously within 6 months.ConclusionThe λ pattern shows promise as a noninvasive biomarker for stratifying neonatal bradycardia and shows potential to guide recovery timeline prediction. Integration of this approach could optimize neonatal arrhythmia management.